Comparison of arterial wave intensity analysis by pressure–velocity and diameter–velocity methods in a virtual population of adult subjects. (November 2020) - Reavette, Ryan M; Sherwin, Spencer J; Tang, Mengxing; Weinberg, Peter D
Pressure–velocity-based analysis of arterial wave intensity gives clinically relevant information about the performance of the heart and vessels, but its utility is limited because accurate pressure measurements can only be obtained invasively. Diameter–velocity-based wave intensity can be obtained noninvasively using ultrasound; however, due to the nonlinear relationship between blood pressure and arterial diameter, the two wave intensities might give disparate clinical indications. To test the magnitude of the disagreement, we have generated an age-stratified virtual population to investigate how the two dominant nonlinearities, viscoelasticity and strain-stiffening, cause the two formulations to differ. We found strong agreement between the pressure–velocity and diameter–velocity methods, particularly for the systolic wave energy, the ratio between systolic and diastolic wave heights, and older subjects. The results are promising regarding the introduction of noninvasive wave intensities in the clinic.